Manassantin B shows antiviral activity against coxsackievirus B3 infection by activation of the STING/TBK-1/IRF3 signalling pathway - Song, Jae Hyoung; Ahn, Jae Hee; Kim, Seong Ryeol; Cho, Sungchan; Hong, Eun Hye; Kwon, Bo Eun; Kim, Dong eun; Choi, Miri; Choi, Hwa Jung; Cha, Younggil; Chang, Sun Young; Ko, Hyun Jeong (Scientific Reports, 2019)
Coxsackievirus B3 (CVB3) is an important human pathogen associated with the development of acute pancreatitis, myocarditis, and type 1 diabetes. Currently, no vaccines or antiviral therapeutics are approved for the prevention and treatment of CVB3 infection. We found that Saururus chinensis Baill extract showed critical antiviral activity against CVB3 infection in vitro. Further, manassantin B inhibited replication of CVB3 and suppressed CVB3 VP1 protein expression in vitro. Additionally, oral administration of manassantin B in mice attenuated CVB3 infection-associated symptoms by reducing systemic production of inflammatory cytokines and chemokines including TNF-α, IL-6, IFN-γ, CCL2, and CXCL-1. We found that the antiviral activity of manassantin B is associated with increased levels of mitochondrial ROS (mROS). Inhibition of mROS generation attenuated the antiviral activity of manassantin B in vitro. Interestingly, we found that manassantin B also induced cytosolic release of mitochondrial DNA based on cytochrome C oxidase DNA levels. We further confirmed that STING and IRF-3 expression and STING and TBK-1 phosphorylation were increased by manassantin B treatment in CVB3-infected cells. Collectively, these results suggest that manassantin B exerts antiviral activity against CVB3 through activation of the STING/TKB-1/IRF3 antiviral pathway and increased production of mROS.
Keywords: Animals; Antiviral Agents; Chlorocebus aethiops; Coxsackievirus Infections; Cytokines; Electron Transport Chain Complex Proteins; Enterovirus B, Human; Female; Furans; Humans; Inflammation Mediators; Interferon Regulatory Factor-3; Membrane Proteins; Mice; Mitochondria; Plant Extracts; Protein-Serine-Threonine Kinases; Signal Transduction; Vero Cells; Virus Replication